Energotropic agents are important to prevent urinary tract infections in children - G.M. Letifov; E.P. Krivonosova; F.Kh. Ausheva (LCC «Medicine-Inform», 2019)
G.M. Letifov1, E.P. Krivonosova1, F.Kh. Ausheva2 1Rostov State Medical University, Rostov-on-Don, Russian Federation 2Republican Clinical Perinatal Center, Nazran, Russian Federation Aim: to provide pathogenic basis for the efficacy of levocarnitine (Elcar®), energotropic agent, in infants and young children to prevent urinary tract infections. Patients and Methods: 50 full-term at-risk infants in the first 5 days of life who were followed up to 3 years (20 boys and 30 girls) born from mothers with anemia stage 2-3 and vegetative dysfunction as well 30 age-matched healthy children (10 boys and 20 girls) were enrolled in the study. At-risk children were divided into 2 subgroups. In subgroup A (n=21), complex basis prophylaxis (i.e., sanation of chronic infections, prevention of microbiota disorders, vitamin therapy) was performed. In subgroup B (n=29), 30% Elcar® (2-3 drops twice daily in infants and 4 drops thrice daily in children under 3 years old) was prescribed in addition to the complex basis prophylaxis. Children received this therapy every year for 2 courses lasting 1 month for 3 years. Kidney sizes and renal blood flow were evaluated in the first 5 days of life and every 6 months up to 3 years. Free radical oxidation system was assessed by serum chemiluminescence of luminol-Н2О2 system. Results: in subgroup A, blood chemiluminescence, i.e., the height of rapid flash (Н=60.14±3.33 mm) and light sum (Sm=460.7±27.41 relative units × 104), reduced in catamnesis (p<0.01 and p<0.001, respectively) but did not achieve the levels in healthy children in 76% of cases. In subgroup B, blood chemiluminescence parameters were similar to these ones in the control group (Н=47.76±2.73 mm, Sm=376.5±18.0 relative units × 104; p>0.05). Conclusion: in at-risk infants, kidney growth delay and poor renal blood flow were demonstrated as compared with healthy children. Elcar® improves renal blood flow in 75% of cases and kidney growth in 80% of cases. Keywords: children, infants, urinary tract infections, oxidative stress, energotropic agents, levocarnitine, Elcar. For citation: Letifov G.M., Krivonosova E.P., Ausheva F.Kh. Energotropic agents are important to prevent urinary tract infections in children. Russian Journal of Woman and Child Health. 2019;2(4):340-345.